Literackie formy graniczne (Weiss – Reznikoff – Grynberg) - Jacek Partyka (Zagłada Żydów)
The article discusses three examples of literature concerning the fate of Jews during World War II, three attempts to bridge the gap between literature and document so as to work out an “optimal” way of writing about the Holocaust. All the texts taken into consideration were written, or rather composed as carefully edited collages of authentic documents. Read together, Peter Weiss’s The Investigation, Charles Reznikoff’s Holocaust and Henryk Grynberg’s Children of Zion illustrate two significant processes: the implication of testimony in ideological causes and the purification of testimony from distorting, overtly political engagements.